The importance of social innovations in the knowledge-based economy in the context of footwear sector solutions (Lodz University Press, 2024)
The prepared scientific monograph entitled The importance of social innovations in the knowledge-based economy in the context of footwear sector solutions is an attempt to further exemplify social innovations by identifying real links between social need and a specific good, service, method and process, in the context of solutions used in the footwear industry. Poland is one of the leading European footwear manufacturers, ranking 7th in terms of production volume in the EU, with a market share of 2.5%. In addition, strong competition is observed in the industry, which is conducive to the emergence of new innovations. The work contains theoretical and practical references to innovations in the industry, such as examples of modifications of footwear materials that have been used in business practice, and their measurable effect is to improve the comfort of using footwear. The authors refer to the environmental aspects of innovation, indicating the directions of utilization of production residues of the footwear and tanning industry, including composites, granules, and biostimulants for plants. The subject matter taken up in the monograph is an important contribution to the development of further scientific research covering the footwear industry and its importance in developing social innovations in Poland and the world. Based on the obtained research results and statistical data analysis, we attempted to outline the prospects for the development of social innovations in the footwear industry until 2050. The book can be an interesting study for practitioners and theoreticians, particularly for scientists representing disciplines such as economics and finance, management sciences, materials engineering, or entrepreneurs looking for opportunities to finance innovation in various areas. Publication was funded by the state budget under the program of the Ministry of Education and Science called “Science for Society” (Poland), project title “The impact of footwear design, materials and proper fit on the health of children and adolescents”, project number NdS/539367/2021/2021, amount of funding 796 964,00 PLN total value of the project 796 964,00 PLN